Some Factors Influencing Legal Continuity in the Age of Enlightenment - A. R. Gubaidullin (Ученые записки Казанского университета: Серия Гуманитарные науки, 2024)
In this article, certain factors that influenced legal continuity during the Age of Enlightenment are discussed. The major processes of the period are analyzed, and the importance of legal traditions as the foundation of legal continuity is highlighted. A brief overview of the key approaches to understanding legal traditions is given. Particular attention is paid to the regional divergences of the Age of Enlightenment, with a focus on its specifics in England and later Great Britain, the German and Italian states, France, Russia, and the USA. It was revealed that all factors can be divided into two groups. The first group includes general conditions, circumstances, and prerequisites, which can be further classified into natural and social ones. Natural factors are largely unaffected by the landscape of the period, while social factors are closely tied to society. The factors pertaining to the Age of Enlightenment are part of the latter group. They are of two types. The first type is not actually related to the legal reality of the period. The second type reflects the Enlightenment political and legal doctrines. Conclusions are drawn about the direct and indirect impacts of these factors on the historical processes. It is also demonstrated that the factors of legal continuity formed a unique combination in each studied society, with their influence apparent even after the Age of Enlightenment.